ANITA DESAI‟S NOVELS AS POST-MODERNIST FEMINIST PROJECTIONS - Iseni, Arburim; Hossain, Md. Amir; Ejupi, Vlera; Siljanovska, Liljana (European Scientific Journal, ESJ, 2014)
For centuries, women in the traditional social order and system have always been considered subservient to men. In patriarchal Bourgeois society, the matriarchal community has been ‗humiliated‘, ‗afflicted‘, ‗silenced‘ and ‗tortured‘ socially and economically. With the post-modernizing age, women began to see the universe with their own eyes and not through the male gaze. In India, with the matriarchal struggle against patriarchy another inner revolution started manifesting itself in literature, especially women’s writings. The voices of women began to vie with those of men. The purpose of our paper is to focus on the feminist message as articulated in Anita Desai‘s well reputed novels, Cry, the Peacock and Where Shall We Go This Summer? Our intent is to examine critically how in the post- modern era Indian women writers in English have highlighted women’s questions. They have raised a fiery voice or initiated an inner revolution against the traditional customs and gender discrimination with a view to equalizing human rights. Considering the femme fatale characters of Anita Desai, one of the most renowned Indian writers writing in English, especially the powerful and domineering female protagonists, Sita and Maya of Cry, the Peacock and Where Shall We Go This Summer? This paper proposes to draw attention to Desai‘s works as exemplary instances of postmodern feminism.